2022
DOI: 10.1140/epjc/s10052-022-10782-3
|View full text |Cite
|
Sign up to set email alerts
|

Shadow and quasinormal modes of the Kerr–Newman–Kiselev–Letelier black hole

Abstract: We investigate the null geodesics and the shadow cast by the Kerr–Newman–Kiselev–Letelier (KNKL) black hole for the equation of state parameter $$\omega _q=-2/3$$ ω q = - 2 / 3 and for different values of the spacetime parameters, including the quintessence parameter $$\gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Even before the first ever observation of the BH shadow in 2019 by the Event Horizon Telescope collaboration [62,63] various authors have studied the shadow of the black hole/compact objects within general relativity and modified/alternative theories of gravity (see, e.g. [64][65][66][67][68][68][69][70][71][72][72][73][74][75][76][77][77][78][79][80][81][82][83][84][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]) and also the authors studied the effect of plasma on the BH shadow in [99][100][101][102][103][104][105]. Observation data on the shadow of supermassive BHs at the center of M87…”
Section: Introductionmentioning
confidence: 99%
“…Even before the first ever observation of the BH shadow in 2019 by the Event Horizon Telescope collaboration [62,63] various authors have studied the shadow of the black hole/compact objects within general relativity and modified/alternative theories of gravity (see, e.g. [64][65][66][67][68][68][69][70][71][72][72][73][74][75][76][77][77][78][79][80][81][82][83][84][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]) and also the authors studied the effect of plasma on the BH shadow in [99][100][101][102][103][104][105]. Observation data on the shadow of supermassive BHs at the center of M87…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of BH shadows for different gravity models and BH solutions can be found in . After the first ever observation of the BH shadows of M87 and Sgr A * in 2019 [19] and in 2022 [21], the observations have been developed by various authors [91][92][93][94][95][96][97][98].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, authors [67][68][69][70][71][72][73] have discussed particle dynamics in BH. Authors [74][75][76] have discussed the BH geometries haven the quintessence field and clouds of strings.…”
Section: Introductionmentioning
confidence: 99%